Analisa Ekonomi terhadap Hukum dalam Pemidanaan Partai Politik melalui Pertanggungjawaban Korporasi dalam Perkara Tipikor - Marbun, Andreas Nathaniel; Laracaka, Revi (Integritas : Jurnal Antikorupsi, 2019)
This article will give some rational and reasonable reasons to answer a question on why it is not necessary to attribute a criminal liability upon a political party, considering the meaningless amount of fine as the main punishment that can be imposed to a corporation which convicted of a crime (corruption). This analysis will be based on economic analysis of law and this article will give some relevant equations and precise calculations to support its stance. However, it doesn’t mean that the authors disagree with punishing a political party whose member has committed a corruption. Instead, an insignificant amount of punishment that the anti-corruption law currently regulates and a large sum of money/ assets that a political party may have, are the main factors that cause inefficient enforcement. Therefore, increasing the amount of punishment in the anti-corruption law is the only solution to create a deterrence effect for a corporation, to deter and disincentivise a corporation that wants to commit a corruption. Keywords: Corruption, Economic Analysis of Law, Criminal Liability, Corporate Criminal Liability, Sentencing Guideline